Imaging patterns of wall thickening type of gallbladder cancer - Soundararajan, Raghuraman; Marodia, Yashi; Gupta, Pankaj; Rana, Pratyaksha; Chhabra, Manika; Kalage, Daneshwari; Dutta, Usha; Sandhu, Manavjit (Clinical and Experimental Hepatology, 2022)
Gallbladder cancer (GBC) has a high incidence in certain geographical regions. Morphologically, GBC presents as a mass replacing the gallbladder, a polypoidal lesion, or wall thickening. The incidence of preoperative diagnosis of wall thickening type of GBC is less well studied. The patterns of mural involvement and extramural spread are not well described in the literature. Additionally, wall thickening in the gallbladder does not always indicate malignancy and can be secondary to inflammatory or benign gallbladder diseases and extracholecystic causes and systemic pathologies. Objective reporting of gallbladder wall thickening will help us appreciate GBC’s early features. In this review, we illustrate the imaging patterns of wall thickening type of GBC.